An investigation of Gender Mainstreaming in Disarmament, Demobolisation, and Reintegration (DDR) Programmes : the case of the Eastern Democratic Republic of the Congo - Mbete, Sithembile (University of Pretoria, 2018)
Mini Dissertation (MSS)--University of Pretoria, 2017.